Improve Design and Analysis for the Drive and Speed Increasing Device of Bicycle - Sun Lihua; Guo Shaofei; Zhou Shijin; Zhang Baoqing (Jixie chuandong)
Aiming at the problem of the low driving efficiency of bicycle and difficulty to improve transmission ratio,the method of using reciprocating pedal drive method instead of traditional drive is proposed based on the analysis of the driving device and transmission structure of the traditional bicycle,by using planetary gear train placed inside the wheel for speeding up,the bicycle wheel reach high speeds with small size diameter is ensured.This structure device is reasonable and proved by simulated analysis of ADAMS software,and it is new view for small size folding design of bicycle.